2016
DOI: 10.1074/jbc.m116.757732
|View full text |Cite
|
Sign up to set email alerts
|

RNA Sequencing Reveals a Role of TonEBP Transcription Factor in Regulation of Pro-inflammatory Genes in Response to Hyperosmolarity in Healthy Nucleus Pulposus Cells

Abstract: Edited by Dennis VoelkerTranscription factor tonicity-responsive enhancer-binding protein (TonEBP/NFAT5) is critical for osmo-adaptation and extracellular matrix homeostasis of nucleus pulposus (NP) cells in their hypertonic tissue niche. Recent studies implicate TonEBP signaling in inflammatory disease and rheumatoid arthritis pathogenesis. However, broader functions of TonEBP in the disc remain unknown. RNA sequencing was performed on NP cells with TonEBP knockdown under hypertonic conditions. 1140 TonEBP-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…Analysis of our previous RNA-Seq studies indicated that NP cells express various plasma membrane bicarbonate transporters of the SLC4 and SLC26 families (GEO Accession #GSE86552) (25). Of the bicarbonate transporters expressed, SLC4A2 (AE2), SLC4A4 (NBCe1), SLC4A7 (NBCn1), and SLC26A4 (Pendrin) had the highest levels.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of our previous RNA-Seq studies indicated that NP cells express various plasma membrane bicarbonate transporters of the SLC4 and SLC26 families (GEO Accession #GSE86552) (25). Of the bicarbonate transporters expressed, SLC4A2 (AE2), SLC4A4 (NBCe1), SLC4A7 (NBCn1), and SLC26A4 (Pendrin) had the highest levels.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, contrary to the general understanding, rates of CO 2 hydration by CAs are substantial enough to contribute up to 100% of total extracellular proton production, a metric often erroneously associated solely with glycolytic lactate/H + production (24). Interestingly, our published RNA-Seq (GEO Accession #GSE86552) and microarray data (#GSE42611) along with other expression studies (GSE49560, GSE24612) show that levels of CA9, CA12 and CA3 expression are the highest in rat NP cells (2528). These studies also show that NP cells express CA2 (cytosolic) and CA5b (mitochondrial) at lower levels while the remaining CA isoforms were undetectable.…”
Section: Introductionmentioning
confidence: 85%
“…TNFα may be involved in maintaining cell viability and matrix homeostasis in the physiologically challenging disc niche that is hypoxic, hyperosmolar, and under mechanical stress . Earlier work from our group found that TNFα expression is maintained in the postnatal NP cells by tonicity‐responsive binding‐protein (TonEBP); this transcription factor controls cell adaptive responses in the hyperosmolar disc environment likely in part by regulating the expression of pro‐survival and anabolic matrix genes . Additionally, complete removal of IL‐1β, another cytokine closely related to disc degeneration, renders mice more susceptible to age‐related disc degeneration, further reinforcing the importance of the physiological role that certain cytokines play in the preservation of disc health .…”
Section: Discussionmentioning
confidence: 99%
“…This alteration results is deregulated overexpression of hTNFα . Organ culture was performed using previously described methods . Briefly, dissected vertebra‐disc‐vertebra motion segments from WT (C57BL6) mice were cultured with or without hTNFα (10 ng/mL) in DMEM (1 g/L glucose) supplemented with 10% FBS for 24 hours ( n = 3 mice/group, six lumbar and nine caudal discs/animal).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation